EXPERTISE IN THE FIELD OF STATE EXPORT CONTROL AS A MECHANISM FOR GUARANTEEING UKRAINE’S NATIONAL SECURITY - Holdberh, Natalya; Ryabchenko, Vasyl (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: this article is devoted to substantiating the role and significance of expertise in the field of state export control as a key mechanism for ensuring Ukraine’s national security. Research methods: the article uses general scientific and special methods of cognition: the dialectical method – to reveal the relationship between state export control and national security; systemic and structural-functional analysis – to determine the place of expertise in the mechanism of state control; comparative legal method – to compare domestic and international approaches to the regulation of export control procedures; formal legal method – to analyze the regulatory framework of Ukraine in the field of export control; statistical and empirical analysis – to summarize the official reporting data of the State Export Control Service and identify trends in its activities. Results: the analysis showed that expertise in the field of state export control is a key tool for ensuring Ukraine’s national security and, at the same time, an important factor in supporting domestic exporters of high-tech products. The regulatory and legal basis for conducting expertise, its types and forms were analyzed, and the principles ensuring the objectivity and legality of the process were identified. Statistical data on the activities of the State Export Control Service were summarized, confirming the systematic and adaptive nature of its work. Problematic aspects of the organization of expertise are identified and directions for improvement are substantiated, including: increasing the transparency and efficiency of procedures, expanding advisory support for exporters, introducing electronic services, and strengthening interagency coordination. Discussion: the results obtained show that expertise in the field of state export control has a dual nature: on the one hand, it is an instrument for ensuring national security, and on the other, it is a factor in creating a favorable environment for the development of domestic exporters. This necessitates finding a balance between strict control and flexible procedures. The study emphasizes that current challenges related to the proliferation of sensitive technologies and external aggression against Ukraine make it necessary to strengthen preventive measures and improve the regulatory framework. At the same time, international experience demonstrates the importance of using electronic tools, transparent mechanisms for interaction with business, and the involvement of non-governmental expert institutions. Thus, the further development of the expertise system should be based on a combination of national security priorities and adaptation to international export control standards.